e-Learning Integrated STEM Education Center (eLISE) in Asia: A Reflection Case Study of Taiwan and Vietnam Research Project - Chang, Chun- Yen; Ling Lin, Pei-; Thị Tố Khuyên, Nguyễn (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective:This article describes the implementation plan, advance and future directions of the academic and educational research center eLISE (e-Learning Integrated STEM Education Center) whose foundation intends to narrow the collaboration between Taiwan and Vietnam in e-Learning and STEM (Science, Technology, Engineering, Mathematics) in the framework of the New Southbound Policy[1], a long-term project announced by the Taiwanese government to strengthen the partnership with South Asian countries. Originality / contribution:This article contributes to the reflection about the promotion of international cooperation in innovation, scientific and technological research as well as the analysis of public policies guided towards e-Learning and STEM innovation. Information collection method / strategies: The stages of the research and innovation process were (1) Innovation e-Learning and STEM Instruction teaching material and module: test application, teacher workshops and interviews (2) Innovation e-Learning and STEM assessment through CloudClassRoom observation with Gamified Electronic Audio Response System and Google Bert.  Conclusions: The description of the implementation of eLISE, the explanation of the development of innovative curriculums and teacher workshops, as well as the talent exchange and the cooperation between industry and academy, highlights the importance of cultivate talents and workforces educated through STEM and e-Learning, seeking regional development and prosperity for both, Taiwan and Vietnam.   [1] Office of Trade Negotiations, executive Yuan, Bureau of Foreign Trade, T. M. of E. A. New Southbound Policy Guidelines and Action Plan. (Taipei, 2017).